PERANCANGAN VIDEO AGROWISATA SAWAH SOLOK SEBAGAI MEDIA PROMOSI - D.RAVI DERAJAT, DERAJAT; Eliya Pebriyeni (Universitas Negeri Padang, 2021)
Solok City is one of the cities in West Sumatra Province which is geographically quite unique, that is, this city has various tourist sites. This diversity gives rise to natural exoticism so that it can be used as a tourist attraction. Therefore, as an introduction to tourism in the city of Solok, West Sumatra as well as to advance the tourism sector in the city of Solok, the authors put it in the form of designing a videography-based agro tourism promotion. The research method used qualitative methods with data collection techniques using observation, interviews, and existing. The concept used in the design is